Interrogating Election Management and Postponements in Nigeria’s Electoral System, 1999-2023 - Nwaodike, Chibuzor Ayodele Nwaodike; Agunbiade, Oluwole Agunbiade (African Journal of Stability and Development (AJSD), 2025)
The conduct of free, fair, and timely elections is considered, worldwide, the most crucial responsibility of an electoral body. In Nigeria, the Independent National Electoral Commission (INEC) bears this duty. It has conducted seven general elections between 1999 and 2023, with four of them being postponed consecutively. Therefore, the study examined election management and postponement within Nigeria’s electoral system from 1999 to 2023. The paper employed a documentary research design based on secondary data and analysed thematically. The study found that elections in Nigeria took on a new dimension and were postponed in 2011, 2015, 2019, and 2023. INEC’s failure to hold elections on schedule was due to institutional challenges, policy inefficiencies, shortages of election materials at polling stations, malfunctioning equipment, technical difficulties, non-deployment of government security agencies, and staff involvement in fraud. These issues have led to disputed results, electoral violence, property destruction, fatalities, and voter apathy. The study concluded that the normalisation of election postponements by INEC has hindered democratic development and weakened democratic consolidation in Nigeria. It recommended enacting legislation to establish a fixed, legally binding date for general elections, strengthening institutional capacity to manage elections efficiently, and fostering collaboration with security agencies to ensure safety during elections.